Occipital nerve stimulation for the treatment of intractable chronic migraine headache: ONSTIM feasibility study - Saper, Joel R; Dodick, David W; Silberstein, Stephen D; McCarville, Sally; Sun, Mark; Goadsby, Peter J (Cephalalgia, 2011)
Background: Medically intractable chronic migraine (CM) is a disabling illness characterized by headache ≥15 days per month. Methods: A multicenter, randomized, blinded, controlled feasibility study was conducted to obtain preliminary safety and efficacy data on occipital nerve stimulation (ONS) in CM. Eligible subjects received an occipital nerve block, and responders were randomized to adjustable stimulation (AS), preset stimulation (PS) or medical management (MM) groups. Results: Seventy-five of 110 subjects were assigned to a treatment group; complete diary data were available for 66. A responder was defined as a subject who achieved a 50% or greater reduction in number of headache days per month or a three-point or greater reduction in average overall pain intensity compared with baseline. Three-month responder rates were 39% for AS, 6% for PS and 0% for MM. No unanticipated adverse device events occurred. Lead migration occurred in 12 of 51 (24%) subjects. Conclusion: The results of this feasibility study offer promise and should prompt further controlled studies of ONS in CM.